Bibliometric Analysis of Hybrid Learning Research Trends in Schools - Emiliyanti, Rantika (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2024)
The aim of this research is to examine how research onhybrid learning in schools. This research method uses a literature review using a bibliometric analysis method approach starting from entering the keyword “pembelajaran hybrid” by setting the search year 2018-2023 and journals using the Publish or Perish (PoP) software application. The database used is Google Scholar, after searching Initially by selecting the keyword "hybrid learning" the maximum search allowed in Google Scholar is 1000 journals and we could enter a value of less than 1000. This research utilizes Publish or Perish (PoP) and VOSviewers software to analyze the data. Based on the findings, results and discussion, it was found that the highest number of scientific publications on the Google Scholar site from 2018-2023 occurred in 2020 and 2021. The results of research based on overlay visualization and density visualization in 2018-2023 centered on hybrid learning variables, meaning that there was a lot of research carried out by other researchers.